How followers’ perception of followership prototype–traits fit impacts their job performance: a moderated polynomial regression analysis - Yu, Jing; Feng, Jian (Frontiers in Psychology, 2024)
Based on the conservation of resources (COR) theory, this study explores whether, how, and when followers' perception of followership prototype-traits fit (followership prototype-traits fit, hereafter) influences their job performance. The results of a time-lagged survey (Study 1) and a scenario-based experiment (Study 2) reveal that: (1) Compared with the misfit, followership prototype-traits fit is more likely to stimulate followers' taking charge; (2) Compared with low levels of fit, high levels followership prototype-traits fit is more likely to stimulate followers' taking charge; (3) Compared with high followership prototype and low followership traits condition, low followership prototype and high followership traits condition is more likely to stimulate followers' taking charge; (4) Followers' taking charge mediates the impact of the followership prototype-traits fit on followers' job performance; (5) The impact of followership prototype-traits fit on followers' taking charge is more salient for male followers than for female followers.